“Thermal, medicinal, mineral, miraculous”: investigating the properties of Caldas da Rainha waters in 18th-century Portugal - Viotti, Ana Carolina de Carvalho [UNESP] (Sociedade Brasileira de Historia da Ciencia, 2024)
Assuming the dual role of both a disseminator of ailments and a virtuous ingredient for curing diseases, waters have been extensively discussed in medical, surgical, and pharmaceutical literature throughout time. Treatises, observations, and warnings abound with references to the benefits of waters or precautions to be taken in their identification and use. In the 18th century Portugal, the analysis of the properties of a specific “type” of water – defined as thermal, medicinal, or mineral – also comes under examination through the lens of emerging chemical science, questioning the “magical” interpretations of their composition. In this context, a specific area in that reign, named precisely after its springs and royal patronage, Caldas da Rainha, receives special attention from a series of scholars, giving rise to significant literature on the topic. Here, in order to systematize this rich body of work, it is presented, in addition to a brief mapping and discussion of the main contours of the theme, the annotated and orthographically updated edition of selected chapters from an anonymous and little-known booklet, written by an empiricist – or, as he titles himself, “a curious individual” – which engages and challenges doctors, apothecaries, and nurses of the time, the Observaçoens das agoas das Caldas da Rainha, from 1752.
“Termais, medicinais, minerais, milagrosas”: a investigação das propriedades das águas caldenses no Portugal do século XVIII
Keywords: 18th century; medicine; pharmacy; thermal waters